THE MOST DOMINANT SOURCE OF STUDENT’S SELF-EFFICACY IN ENGLISH PUBLIC SPEAKING - Tri Setyaningsih; Nurhandayani Supraptiningsih; Farah Andina Utiarahman (ELLTER Journal, 2022)
The objectives of this research are to investigate the most dominant source of self-efficacy that affects students’ English public speaking skills and to discover the students’ strategies in developing their self-efficacy. Moreover, this research is conducted among fourth semester of public speaking students consisting of 32 participants. In this case, the researchers use the descriptive qualitative method to calculate the data gathered. The finding reveals that the main source of self-efficacy that affects students’ public speaking skills is the Psychological and Affective States. Another finding also shows that varied strategies are elaborated in order to develop self-efficacy, such as getting the assistance from teacher’s feedback, finding friends as role model, being noticed by peers, and being able to control physical and emotion stress reactions.